An intervention study of autologous fat transfer for scar tissue rejuvenation in the setup - Parikh, Nirzaree K.; Darshan, Jitendra R. (International Surgery Journal, 2018)
Background: There are lot of work going on AFT procedures. This procedure has been taken recent advances nowadays and very helpful in many conditions to rejuvenate and restoration of damaged tissues. The use of autologous fat for soft tissue augmentation seems attractive because of its relatively ubiquitous availability. Autologous fat transfer is a technique shown to be beneficial as a reconstructive procedure for patients with volume loss of tissue due to disease, trauma, and congenital defects. Methods: In the present study, 20 patients were taken as sample size. It is an intervention study. Whole procedure has been taken as day case which included local anaesthesia and patient received all the standard monitoring, medications, safety precautions and care that is provided for any patient undergoing any surgery, including antibiotics, pain medicine and other supportive care as needed. The Autologous fat was harvested by surgeon via syringe aspiration technique with a long atraumatic cannula. After processing, the material was injected immediately under designated skin grafts/scars using a small needle. Scar was cleansed with normal saline and dry dressing is applied for a day. Then patient was discharged on the same day. Results: Results obtained were efficacious with 60 to 80% improvement in all parameters in 15-20 days after the procedure. Conclusions: AFT procedure was found feasible, efficacious and accepted in patients with scar. It brings scar tissue rejuvenation up to great extent.